Regulatory Architectures and Market Structuring in ASEAN Digital Platform Ecosystems - Lita Wulantika (Manexia: Journal of Business, Management, and Creative Economy, 2025)
The rapid maturation of digital platform markets in Southeast Asia has coincided with intensified regulatory development across the region. While existing platform research emphasizes network effects and governance design, limited attention has been given to how regulatory systems actively structure ecosystem configuration. This article develops a mechanism-based framework explaining how regulatory architectures shape digital platform ecosystems in emerging economies. Rather than conceptualizing regulation as an external constraint, the study reframes it as an institutional infrastructure that organizes market participation, redistributes governance control, and reconfigures complementarities among interdependent actors. The framework identifies four architectural dimensions—entry structures, data governance boundaries, interoperability standards, and enforcement intensity—and specifies five structuring mechanisms through which they influence ecosystem outcomes. These mechanisms explain variations in ecosystem concentration, value capture distribution, cross-border scalability, and innovation directionality. By integrating institutional theory, ecosystem strategy, and nonmarket strategy perspectives, the article advances a structurally grounded understanding of how markets are organized in digitally mediated environments. The analysis offers theoretical contributions to institutional and platform scholarship while outlining managerial and policy implications for emerging digital economies navigating regulatory consolidation.